Academic freedom in Singapore and the "fake news" law - Teo, You Yenn (Observatory Southeast Asia Ltd, 2022)
The Singapore government is seeking to pass new legislation to deal with “fake news” and misinformation on the Internet. Critics have already raised concerns about freedom of expression and press freedom, but less discussed thus far are issues related to academic freedom in the city-state.